Hipoglikemia Pada Pasien Diabetes Melitus - Mesa Sukmadani Rusdi (State University of Gorontalo, 2020)
Diabetes mellitus (DM) is a metabolic disorder characterized by an increase in insulin due to decreased insulin secretion by pancreatic beta cells and/ or insulin resistance. Hypoglycemia is one of the main risks that DM patients often to suffer. in Type 2 DM, hypoglycemia is the most common side effect of the use of insulin and sulfonylureas. It is because of their modes of action . Hypoglycaemia presents a major barrier to satisfactory long term glycemic control and remains a feared complication of diabetes treatment. Acute and chronic complications of hypoglycemia can interfere with life, such as social interactions, sleep, sexual activity, driving, sports, and other activities. Blood glucose monitoring needs to be done to prevent the risk of hypoglycemia. Patients treated with insulin, sulfonylureas/glinides are advised to check blood glucose any time hypoglycemia is going to happen.